Criticism of Fatima Mernissi's Understanding of Misogynistic Hadith on Women's Leadership - Farid Fauzi; Firdaus Firdaus; Yosi Ariyanti; Yusrial Yusrial; Awang Ringgit (Ri'ayatu Al-Qur'an: Jurnal Pendidikan Islam, 2024)
Discussions on women's leadership in various areas of life attract the attention of many groups; both fuqaha, mufassir, and hadith experts. Differences of opinion are inevitable. The basis of this debate stems from an understanding of the hadith which textually seems to prohibit women from becoming leaders. This scientific article presents the debate on women's leadership based on the hadith texts of the Prophet Muhammad and the views of hadith scholars, mufassir and fuqaha. In fact, leadership is not in terms of mahdhah worship or rituals that do not recognize sex or gender. Leadership demands competence or skill and a person's worthiness in leading, not gender.